2007
DOI: 10.1002/ijc.22990
|View full text |Cite
|
Sign up to set email alerts
|

Risk of endometrial cancer in relationship to cigarette smoking: Results from the EPIC study

Abstract: Current epidemiologic evidence indicates that cigarette smoking reduces the risk of endometrial cancer. We examined data from the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort to analyze further aspects of the smoking-endometrial cancer relationship, such as possible modifying effects of menopausal status, HRT use, BMI and parity. In a total of 249,986 women with smoking exposure and menopausal status information, 619 incident endometrial cancer cases were identified during 1.56 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
35
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 37 publications
13
35
2
Order By: Relevance
“…In our study, smoking women had a decreased risk of endometrial cancer, which is in agreement with other prospective cohort studies (Terry et al, 2002;Viswanathan et al, 2005;Al-Zoughool et al, 2007;Loerbroks et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, smoking women had a decreased risk of endometrial cancer, which is in agreement with other prospective cohort studies (Terry et al, 2002;Viswanathan et al, 2005;Al-Zoughool et al, 2007;Loerbroks et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Differences in the BMI distribution across studies are a potential source of heterogeneity when expressing results on a linear scale, as it ignores that the true relationship between the logarithm of the relative risk and BMI is probably not linear. Smoking may be an additional confounder as it is antiestrogenic (58) and there is evidence that the risk of endometrial cancer is attenuated for a given BMI category in smokers compared with nonsmokers (59,60). However, the present analysis was not designed to assess the complex triangulated relationship of BMI, HRT, and smoking, and indeed our search failed to identify a study that assessed all three risk factors interactively.…”
Section: Confounding and Biasmentioning
confidence: 99%
“…The increased enzyme activity results in greater clearance of estrogens from the circulation and a reduction in end organ effect 102 . Epidemiological studies have demonstrated a 20-30% reduction in the risk of endometrial cancer in women who smoke 103,104 . Endogenous estrogen production also occurs via autonomous synthesis within some ovarian tumors.…”
Section: Role Of Estrogen In Endometrial Carcinogenesismentioning
confidence: 99%